Spontaneous coronary artery dissection in cardiac sarcoidosis. Issue 5 (31st May 2019) - Kandolin, Riina; Ekström, Kaj; Simard, Trevor; Hibbert, Benjamin; Nery, Pablo; Lehtonen, Jukka; Kupari, Markku; Birnie, David
Abstract: Cardiac sarcoidosis (CS) is increasingly recognized as a cause of diverse cardiac manifestations. Spontaneous coronary artery dissection (SCAD) has emerged as an important cause of acute coronary syndrome especially among young females. The prevalence of sarcoidosis in the causal spectrum of SCAD has not been described before but sarcoidosis is cited as a potential yet rare cause of SCAD. We aimed to examine the frequency and characteristics of SCAD in CS. Searching two prospective CS registries with 481 CS patients, we found only one case of manifest SCAD. She is a 61-year-old female previously diagnosed with endomyocardial biopsy confirmed CS. She presented with chest pain and elevated troponin. Coronary angiogram revealed two-vessel SCAD. Fluorodeoxyglucose positron emission tomography scan showed likely reactivation of CS. The patient was treated with dual antiplatelet therapy and immunosuppression. Repeat angiogram showed complete resolution of the coronary lesions.